(3QSGdI bGFe GdReGf hGdgGOi dWQjb GdQMefs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3aeG cGf ef UhGH hLRGdI NWGH aHHQcGJg hGdJeSc HMOhOg hBjGJg heG cGf ef NWC ChRdd aef YLRi hJbUjQi s
(3BNQgG (B:s
(3hGaVd GdYGde ai CaVd ReGf aYdjce HWGYI MOhOce heYQaI eYHhOce JQTOhG hJhabhG hGdehdi Ydi cd TF bOQ hgh MSHi hfYe GdeYjf GdfUjQ ai LejY GdCehQ JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B66s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis